Supply chain hierarchical position and firms' information quality - BAI, Xuelian (Institutional Knowledge at Singapore Management University, 2020)
This study examines the relation between a firm's supply chain hierarchical position and its information quality. We predict that firms located in a more upstream position within the supply chain network are exposed to greater demand variance, thereby leading to decreased quality of reported earnings and greater uncertainty in the public information available to investors. Consistent with this prediction, we find that firm's vertical position in the supply chain network is negatively associated with its information quality (i.e., poorer earnings quality and higher stock return synchronicity). Our results are robust to the matched sample analysis, residual analysis, and alternative measures of information quality. We further show that the positive relation between firm's hierarchical position and stock return synchronicity is more pronounced for firms facing higher information asymmetry. Overall, our findings suggest that a more upstream position in the supply chain network entails not only operational costs associated with amplified demand uncertainty but also costs related to the quality of reported information on which capital providers and other stakeholders rely.